Jackknife versus Lithotomy Position for Hemorrhoidectomy Surgery: A Randomized Controlled Trial - Sina Ghasemi; Behzad Imani; Alireza Jafarkhani; Ashkan Karimi; Ali Yamini (مجله علمی دانشگاه علوم پزشکی کردستان)
Background and Objective: Hemorrhoids are known as one of the most common anorectal diseases and the most common cause of lower gastrointestinal bleeding. Investigating which type of technique and approach the surgeon has more expertise during hemorrhoidectomy surgery and the patient faces fewer complications is crucial. Therefore, this study evaluated the effects of the Jackknife and Lithotomy positions on the course and complications of hemorrhoidectomy surgery. Materials and Methods: The present study was a clinical trial conducted on 60 patients with hemorrhoids at Besat Hospital in Hamedan. The patients were randomly divided into two groups of 30. The first group underwent surgery using the Jackknife position, while the second group underwent the conventional method using the Lithotomy position. Finally, variables such as the amount of bleeding, duration of surgery, surgeon's field of view, local posture discomfort, and postoperative pain were analyzed and compared between the two groups using SPSS software version 24. Results: 22 (36.7%) of the patients were male and 38 (63.3%) were female. According to the findings, the duration of surgery and the amount of bleeding were less in the group undergoing surgery with the jackknife position, and a significant difference was observed between the surgical position and these two variables (p-value<0.001). Also, based on the chi-square test, there was a statistically significant relationship between the surgical position and the surgeon's satisfaction with the angle of view, so a better field of view was reported in the jackknife position (exact p-value = 0.001). In this study, no significant difference was observed between the surgical position and the level of local posture discomfort of the surgeon and between the surgical position and the postoperative pain complication (significance level 0.091 and 0.66, respectively). Conclusions: Performing hemorrhoidectomy surgery with the Jackknife position compared to the Lithotomy position can reduce the amount of bleeding in patients, shorten the duration of surgery, and provide a better field of view and exposure for the surgeon. Additionally, based on the findings, using either position does not significantly impact the level of local discomfort or postoperative pain.